Controlling factors in economic development - Moulton, Harold G. (Brookings Institution, 1949)
This book introduce the nature of a synthesis of the economic studies in which the author has participated during the last thirty years. Such an interpretative treatise was conceived as an ultimate objective at the time the brookingd institution was established and its broad program of nivestigation was organized.